Perceptions of 6 members of community centi about learning english based on christian religion at the people fundation (2015)
The results that were obtained in a study of a group belonging to the population are presented CENTI, about influences, perceptions, needs and benefits of learning the English language with a Christian approach based on a course offered by the People Foundation. This study, through a qualitative research, it was revealed general and particular aspects of how to learn a second language involves different personal and spiritual benefits to the members of a religious community. Samples were taken with different data collection instruments such as surveys, focus group and video recordings, which, brought different opinions, perspectives and considerations of each of the members. Throughout the thesis, different variables were generated and concluded from qualitative results and demonstrated the important factors and imaginary parameters that lead each individual to be part of the service offered by the People Foundation; They agreed on the cultural, social, religious, academic and professional importance to people who have access to such education, which consequently will bring monetary benefits, job opportunities, ability to communicate with different cultures and the ability to manifest the word of God